1995
DOI: 10.23986/afsci.72619
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed dressing treatment of Streptomyces griseoviridis on barley and spring wheat in field experiments

Abstract: The effect of seed dressing with the antagonist Streptomyces griseoviridis on root rots and yields of wheat and barley was studied in field experiments. In long-term field experiments, where different levels of soil-borne inoculum of root rots were maintained with different crop sequences, seed treatment with the antagonist increased yields slightly on average over all experimental years. However, variations between years, crops and crop sequences were considerable. The highest yield increases were in excess o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…When comparing seed lots FSS >2.7 mm and FSS >2.7 mm + dis , seed disinfection increased grain yield by 300 kg ha -1 . This yield improvement is comparable with the results presented previously in other Nordic studies (Tahvonen et al 1995, Johnsson et al 1998). CCS and FSS >2.7 mm + dis attained a slightly lower grain protein concentration (%) as compared with other seed lots (Table 2).…”
Section: Resultssupporting
confidence: 93%
“…When comparing seed lots FSS >2.7 mm and FSS >2.7 mm + dis , seed disinfection increased grain yield by 300 kg ha -1 . This yield improvement is comparable with the results presented previously in other Nordic studies (Tahvonen et al 1995, Johnsson et al 1998). CCS and FSS >2.7 mm + dis attained a slightly lower grain protein concentration (%) as compared with other seed lots (Table 2).…”
Section: Resultssupporting
confidence: 93%
“…It is possible that the root exudates of carrot lack some characteristics necessary for the prolifération of S. griseoviridis. The efficacy of S. griseoviridis seed dressing on barley and spring wheat against foot rot disease was investigated by Tahvonen et al (1994) who demonstrated that wheat yields can be increased by seed dressirigs more efficiently than those of barley. Juhnke et al (1987) tested the rootcolonization ability of bacteria on wheat in fields and found that compared to other rhizobacteria, Streptomyces species were poor colonizers.…”
Section: Plant Colonization and Biocontrolmentioning
confidence: 99%
“…Evidence for production under more natural conditions was difficult to obtain, possibly due to problems associated with adsorption of the antibiotics to clays and the very small amounts likely to be produced in oligotrophic environments such as soil (43). Streptomycetes have been recommended for the biocontrol of fungal root and seed pathogens (15,37) but are better known as prolific producers of commercially important clinical antibiotics (22).…”
mentioning
confidence: 99%